CONTRIBUTING FACTORS TOWARDS DIFFICULTIES IN GENERATING IDEAS AMONG TECHNICAL STUDENTS - Heong, Yee Mei (Journal of Technical Education and Training, 2013)
Idea is a thought or collection of thoughts that are important to decision making and problem solving. The purpose of this research was to analysis the factors contributing to difficulty in generating ideas among technical students. A total of 375 technical students from four technical universities in Malaysia were randomly selected as samples. A set of questionnaires was developed and used as research instrument. The findings indicated that a total of 319 (85.1%) technical students faced difficulties in solving individual assignments. Most of the problem faced by technical students is the difficulty of generating ideas for solving individual assignments. The most difficult individual assignment is critical review or summary of articles. Deadlock of ideas is the most important factor in the difficulty to generate ideas among technical students. A total of 261 students (69.6%) also believed that the difficulty of generating ideas is a key factor affecting the achievement of the students’ assignments. As a result, difficulties in generating ideas lead to students having problems in completing their assignment. Therefore, students need to learn higher order thinking skills which are essential skills enabling students to generate ideas and consequently complete assignments